2007
DOI: 10.1007/s00134-007-0905-7
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia in neurological patients: cerebral salt wasting versus inappropriate antidiuretic hormone secretion

Abstract: The adequate blood volumes in hyponatremic patients confirm the diagnosis of SIADH and do not support the concept of CSWS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 21 publications
0
40
0
3
Order By: Relevance
“…Second, we cannot be certain that the patients we included did not have a RSWS rather than a SIADH. The existence of the RSWS is controversial as suggested recently by Brimioulle et al [25] who demonstrated no difference in red blood cell, plasma and blood volumes between hypo- and normonatremic ICU patients. Even if the existence of this entity remains under debate due to conflicting conclusions from different studies, treatments are theoretically opposite with infusion of fluids and Na in the salt-wasting syndrome and fluid restriction for SIADH.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we cannot be certain that the patients we included did not have a RSWS rather than a SIADH. The existence of the RSWS is controversial as suggested recently by Brimioulle et al [25] who demonstrated no difference in red blood cell, plasma and blood volumes between hypo- and normonatremic ICU patients. Even if the existence of this entity remains under debate due to conflicting conclusions from different studies, treatments are theoretically opposite with infusion of fluids and Na in the salt-wasting syndrome and fluid restriction for SIADH.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,4 A postulated mechanism of hyponatremia influencing outcome also in neurointensive care could be its relation to an increased nonosmotic release of AVP caused by the overstimulation of the neurohumoral axis or by baroreceptor failure in elderly patients leading to cerebral hypoperfusion. 11,28 After severe neurotrauma such as ICH, increased intracranial pressures and cerebral hypoperfusion may even aggravate secondary brain injury. Assuming that these mechanisms play a role in patients with ICH, increased AVP levels themselves could contribute to a reduced tolerance to cerebral hypoxia.…”
Section: May 2014mentioning
confidence: 99%
“…To shed some light on this controversy, Brimioulle et al prospectively investigated whether hypotonic hyponatremia is associated with SIADH or CSWS in patients with acute neurological disorders with normal renal function and clinically normal fluid status. These authors concluded that adequate blood volumes in hyponatremic patients confirm the diagnosis of SIADH and do not support the concept of CSWS [10]. The distinction is furthermore not important in children with TBM as hyponatremia complicating intracranial disease should always be treated with hypertonic saline (regardless of volume status) [6].…”
Section: Tb Meningitis and Hyponatremiamentioning
confidence: 95%